Where in the world should I invest : an insider's guide to making money around the globe - Rahemtulla, Karim (Hoboken, N.J. : Wiley, 2012)
'A fascinating exploration of which countries offer promising investment opportunities for Americans now and in the years to comeMost emerging markets investment guides focus on financial metrics, but fail to provide the reader with new and relevant insights into the history of the countries, the views of the people on the street, and the financial shenanigans that go on behind the scenes, that make for truly informed investing. As a result, despite the growing interest in investing in these markets, investors are often missing key opportunities because they either have incorrect information about a country where they might invest, or simply don't know what questions they should be asking. Where In the World Should I Invest: An Insider's Guide to Making Money Around the Globe is here to help.Drawing on author Karim Rahemtulla's personal experiences traveling the globe and exploring the capitals where business is transacted, the book outlines the perils, pitfalls, and rewards of investing in'low float' markets. The essential resource for taking the right steps in exploring investment opportunities in foreign and emerging markets Expert advice from an author with 20 years experience covering emerging markets Commentary on the expectations of foreign investors, the fears of investing abroad, how to set up legal offshore accounts, and much more Packed with unique insights into twenty countries and regions around the globe based on the author's extensive interviews and travels, Where In the World Should I Invest is a must-read for anyone thinking of expanding their investment portfolio overseas'--
Includes index.
Keywords: Investments, Foreign; Investments; BUSINESS & ECONOMICS / Investments & Securities